MANAJEMEN MUTU PENDIDIKAN MAN INSAN CENDEKIA - Apud Apud (Tarbawi, 2018)
The writing is based on research which describes educational quality management of MAN Insan Cendekia as one of madrasas which performs boarding school system focused on academic programs. The research findings are: The first, implementing quality management at boarding school begun with formulating strategic planning/school framework with certain steps: analysis, formulating program draft, socialization, budgeting, and documentation. The process also determines the school programs those are academic, studentship, boarding, facility and media, and networking. The second, the steps of implementation strategy are implementing and evaluating educational program quality. (1) Implementing educational program quality of boarding school begun with the procedures of socializing quality program plan, technical plan, implementation program, monitoring, supervising, and evaluation with bottom up-top down approach; (2) evaluating educational program quality systematically begun with the procedures of self-evaluation, quality internal audit, teacher’s competence evaluation, management evaluation, and external audit. The third, the supporting factors and the constraint ones in implementing educational quality management correlated with raw input, teachers, budgeting, leader’s commitment to quality, facilities, learning environment, and networking. The fourth, the strategic way to improving the educational qualities are integrating school program with boarding programs, formulating life directions, upgrading human resources and facilities/media, building school culture, and networking. Keywords. madrasa, boarding school, management, quality.